Virtual Private Cloud (VPC) & Elastic Compute Cloud (EC2) with Remote Access Using PuTTY Terminal on Ubuntu in a Private VPN - Syahputra, Irwanda; Akram, Rizalul (Journal of Advanced Computer Knowledge and Algorithms, 2024)
One of the computer technologies that is commonly used by agencies/companies is the internet network which functions as a bridge to connect between one point to another. Apart from having the advantage of being a medium for long-distance communication, the internet also has a lack of security. One of the weakness found is the internet as a transmission medium for important or confidential data. One effort that can be made to overcome this problem is to build a private network in a public network service, which is often known as a Virtual Private Network (VPN). In this research, the VPN was built by combining a Virtual Private Cloud (VPC) with Elastic Compute Cloud (EC2) and using Ubuntu's Terminal in PuTTY Gen as remote access using network protocols for remote server needs from remote control.